MISLEADING POSITIONS OF GEOMAGNETIC REVERSAL BOUNDARIES IN EURASIAN LOESS AND IMPLICATIONS FOR CORRELATION BETWEEN CONTINENTAL AND MARINE SEDIMENTARY SEQUENCES - Zhou L.P.; Shackleton N.J. (My University, 1999)
The Matuyama–Brunhes boundary (MBB) where the Earth's magnetic field changed to its present orientation is one of the most frequently used time markers in continental Quaternary stratigraphy. Although magnetic signals have been successfully recovered from loess deposits and an apparently coherent magnetostratigraphy seems to be in place, a close examination of the published loess records from northern mid-latitudes reveals significant uncertainty and variability for the position of the MBB. In Asia and part of Central Europe, the MBB has been found in loess, a glacial deposit. This is in contrast to the well-established palaeomagnetic records in deep-sea sediments where the MBB is located in the interglacial Oxygen Isotope Stage 19. This discrepancy has caused serious confusion in stratigraphic correlation between loess and marine sequences. Here we examine the causes of the discrepancy between the two sedimentary environments in their records of the MBB. Our approach includes a comparison of the MBB in loess and other continental records, and an evaluation of the stratigraphic significance of the microtektites found around the MBB. Based on the occurrence of the MBB in an interglacial stage in lake and continental margin sequences and the correlative stratigraphic positions of the microtektites in marine sediments and loess, we demonstrate that the measured positions of the MBB in loess are erroneous and misleading, and its true occurrence was during the time of formation of the palaeosol corresponding to Oxygen Isotope Stage 19. The most plausible cause for the apparent offset, i.e. the MBB being found in the underlying loess instead, is that the acquisition of remanent magnetisation in loess occurs at a certain depth substantially below the land surface. The degree of such displacement is dependent on the lithology and structure of the deposits formed prior to the reversal, and the time delay is estimated to be in the order of 103–104 years. We show that other geomagnetic boundaries, such as those of Jaramillo and Cobb Mountain, in loess have been similarly displaced though to a varying extent. We suggest that the remanence acquisition in loess is closely related to the post-depositional evolution in the structure of loessic materials which is in part influenced by regional climate conditions. Our conclusions on the displaced remanence acquisition have implications for loess chronology, magnetostratigraphy as well as the geomagnetic interpretation of detailed magnetic signatures from loess.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная